Halal Industry during the Covid-19 Pandemic is The Hidden Blessing: Industri Halal Selama Pandemi Covid-19 Adalah Berkah Tersembunyi - Ana Toni Roby Candra yudha; Abdullah Kafabih (El-Qist: Journal of Islamic Economics and Business (JIEB), 2021)
The MSMEs-based halal industry is one of the sources that should be taken into account to be developed. This study aims to provide a comprehensive review and analysis of the halal industry and micro, small and medium enterprises (MSMEs) in their efforts to maintain economic resilience during a Covid 19 pandemic. This analysis focuses on theoretical, established and empirical reviews that focus on the halal industry as a new fiscal source. This study uses a literature study review approach for the halal industry from various literature on the halal industry and MSMEs from Indonesia and overseas. The literature is also limited to the publication of 2015-2020. The findings of this study are that halal industry is the newest source of Islamic economics that can be relied on in raising the country's fiscal. Of course, it is intended for poverty alleviation, distribution of consumption, public service media and other relevant instruments. However, the halal industry integration system can become a "new engine" in economic fundamentals that needs synergy and support from various parties from the government, SMEs, and private sector so that the real issues and conditions for economic recovery amid the pandemic can be better. Keywords: Halal Industry; Post-pandemic; Covid-19; Blessings Abstrak: Industri halal berbasis UMKM merupakan salah satu sumber yang harus diperhatikan untuk dikembangkan. Kajian ini bertujuan untuk memberikan ulasan serta analisis yang komprehensif tentang industri halal dan usaha mikro, kecil dan menengah dalam upayanya menjaga ketahanan ekonomi di tengah pandemi Covid 19. Analisis ini fokus pada ulasan teoritis, kebijakan yang telah ditetapkan dan empiris yang menitikberatkan pada industri halal sebagai sumber fiskal baru. Penelitian ini menggunakan pendekatan kajian kepustakaan industri halal dari berbagai literatur industri halal dan UMKM baik yang berasal dari Indonesia maupun dari luar negeri. Literaturnyapun dibatasi dengan durasi terbitan tahun 2015-2020. Penemuan dari studi ini adalah industri halal adalah sumber terbaru ekonomi Islam yang dapat diandalkan dalam menggalang fiskal negara. Tentunya diperuntukkan untuk pengentasan kemiskinan, pendistribusian konsumsi, media layanan publik dan instrumen lain yang relevan. Namun sistem integrasi industri halal untuk menjadi ‘new engine’ dalam fundamental ekonomi perlu sinergi dan dukungan berbagai pihak dari pemerintah, UKM, dan swasata. Sehingga isu dan kondisi riil pemulihan ekonomi di tengah pandemi dapat lebih baik. Kata Kunci: Industri Halal; Pasca Pandemi; Covid-19; Berkah